Projeto experimental de publicidade e propaganda : ONG Penélopes Solidárias - Colaço, Jéssica Fátima da Rosa (2018)
This paper aims to develop communication planning for the Penelope Solidarity Non-Governmental Organization in the 12-month period. In order to reach this objective, this study was divided in three stages, where in the first stage are the information subsidies, which were obtained through a focus group, in-depth interview and theoretical reference. In the second step was done the communication campaign planning, which defined the objectives, strategies and advertising tactics. Finally, in the third stage, the creations and productions for the campaign were developed.